(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper aims to find suitable short activities for enhancing speaking skills in two languages (i) English and (ii) Arabic of the targeted Tamil medium students from two colleges (i) The New College and (ii) Kilakarai Bhukari Alim Arabic College. The learners who come from Tamil medium background need to be encouraged at the entry level of their higher studies because they face difficulties in communicating their ideas in English or Arabic. These activities will support the learners to speak independently by generate words and sentences on their own. Ten short activities are applied and tested in the selected classrooms in two colleges. The positive feedbacks have been received from the students which ensure that good results in their speaking skills after the implementation of the activities.